Kepemimpinan Demokratis Kyai dalam Mengembangkan Kecerdasan Emosional Santri di Pesantren Tahfidz Nurul Huda Sukabumi - Rifa Zakiah Mahmudah; Mulyawan Safwandi Nugraha (Student Scientific Creativity Journal, 2023)
This research is motivated by the condition of santri in Islamic boarding schools who still do not have good emotional intelligence. Some indicators such as not having high self-confidence, empathy for others and the environment, controlling emotions of sadness and anger. This is certainly contrary to the objectives of education in Islamic boarding schools which in fact have a noble character. The author wants to know the democratic leadership factors that are applied can affect the emotional intelligence of santri. The purpose of this study is to describe the democratic leadership of the kyai in developing the emotional intelligence of students at the Tahfidz Nurul Huda Islamic Boarding School, Sukabumi Regency. This research is a type of qualitative research with a case study approach. The results of the research are that democratic leadership can develop the emotional intelligence of students at the Tahfidz Nurul Huda Islamic Boarding School. Of course this doesn't work instantly, you need continuous mental training. For Kyai as caregivers of santri to always be role models and santri can develop their emotional intelligence even better.